Abuse of Human Rights in Myanmar: An Urgent Appeal to Reinterpret the ASEAN Non-Interference Principle - Arifin, Saru (Human Rights in the Global South (HRGS), 2022)
This article seeks to interrogate the legal and normative tensions between ASEAN’s principle of noninterference and its human rights obligations, using the Myanmar crisis as an illustrative case. While ASEAN has increasingly engaged with human rights discourse through institutional mechanisms such as the ASEAN Intergovernmental Commission on Human Rights (AICHR), its rigid adherence to noninterference has impeded meaningful regional responses to widespread rights violations. Although previous research has acknowledged the inherent tension between state sovereignty and human rights, limited attention has been given to how ASEAN’s legal architecture structurally reinforces state dominance at the expense of individual and collective rights. The study contributes to Global South human rights scholarship by evaluating the internal contradictions within ASEAN’s legal instruments, foundational documents, and institutional practices through a doctrinal legal research approach. It deconstructs the normative logic that positions state sovereignty above human security, revealing how ASEAN’s traditional interpretation of noninterference maintains a status quo that marginalises rights holders and shields regimes from accountability, even in the face of atrocities such as those unfolding in Myanmar. Findings indicate that ASEAN’s state centered model of sovereignty weakens its normative legitimacy and generates legal paralysis in response to human rights crises. The article calls for a reconceptualisation of sovereignty in regional governance, from a regime based to a people centered paradigm, grounded in the recognition that sovereign authority ultimately resides with the people. Such a shift would align ASEAN with evolving global human rights norms and enhance its credibility as a regional rights protecting body. By synthesising legal analysis with normative theory, the article advances a novel framework for reimagining regional human rights governance in the Global South, emphasising the need to prioritise human dignity over political expediency.